A Systematic Review of Endoglin Gene Expression in Preeclampsia. (April 2013) - Bell, Mandy J.; Conley, Yvette P.
Objective: To synthesize scientific literature that addresses the role of endoglin (ENG) gene expression in preeclampsia (PE). Data sources: A literature search of PubMed and Ovid MEDLINE was conducted using the keywords endoglin, gene, and preeclampsia . Restrictions included English language and humans. Additional articles were identified/selected for evaluation via PubMed e-mail updates (keywords: endoglin and preeclampsia ) and review of article reference lists obtained from the search. Study selection: The initial 14 abstracts retrieved from the literature search were reviewed and 9 studies were selected for evaluation. Review articles and studies not addressing ENG expression (messenger RNA [mRNA] level) in the context of PE were excluded. An additional six articles were selected from PubMed e-mail updates and reference lists. Data extraction: Data related to study objective, design, setting, subject information, phenotype, tissue type, data collection method, statistics, and results were extracted. Data synthesis: Regardless of PE definition, ancestral background, gene expression analysis method, tissue type, and time of specimen collection, endoglin appears to play a role in PE development. Moreover, results suggest that a variety of biological mechanisms have the ability to modulate ENG expression in PE, demonstrating the potential complexity associated with endoglin's role in PE. Conclusions: This review article is the first to systematically synthesize evidence related to ENG expression in PE. Findings can be utilized to design future studies that (a) address methodological limitations observed in the reviewed studies and (b) specifically examine why ENG expression levels are altered and address mechanisms explaining how these alterations are involved in PE development.